Is there a transfer of resources from developing to industrial countries? - Rigmar Osterkamp (Intereconomics, 1990)
One of the arguments put forward to support the claim that an unfavourable world economic environment is impeding effective structural adjustment in developing countries is the premise that the flow of resources to indebted developing countries is not only insufficient but also declining and has actually been negative for some years. This leads to the demand for a politically guaranteed positive transfer of resources. Is this demand justified?
Keywords: 330; North-South Relations